SIGNIFICANCE OF ROBOTIC CHOLECYSTECTOMY OVER LAPAROSCOPIC CHOLECYSTECTOMY IN THE MANAGEMENT OF CHOLECYSTITIS: A CASE STUDY OF FACTORS INFLUENCING PATIENTS’ DECISION AT A HOSPITAL IN TEXAS, USA - Ahuja, Vikrom (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
The increasing cases of cholecystitis (gallbladder inflammation) among the patient population call for more corrective measures to improve clinical outcomes. Notably, LC (laparoscopic cholecystectomy) was the standard surgical procedure for managing gallbladder ailment. However, with technological advancement, a robotic-aided technique (robotic cholecystectomy) was introduced based on the idea that it improves on some of the shortcomings associated with LC. Notably, RC involves a single incision, hence, it is less invasive than LC. The research objectives aim at establishing the RC's clinical significance over LC. It also analyzes the factors that inform patients' decisions regarding their preferred cholecystitis management procedure. A literature review of the current scholarly information on the subject was conducted to gather insights that somehow informed the study. The researchers employed a descriptive and explanatory research design based on mixed methods (quantitative and qualitative ones). Besides, the target population for this study was selected from Memorial Hermann Hospital in Houston, Texas. Although the scholars had projected a 292 sample size based on the Yamane formula, they gathered 350 voluntary participants comprising 250 cholecystitis patients and 100 surgical unit healthcare professionals. The data collection tools included surveys and interviews. The collected information was analyzed using MS Excel and SPSS statistical tools. The findings showed that cholecystitis patients analyzed factors such as the degree of pain, cost, postoperative complications, operation duration, scarring, and recuperation rate before making decisions. RC proved to have more benefits than LC. However, LC was still preferred in some cases because it is cheaper and takes less surgical time.